Preaching : how to preach biblically - MacArthur, John, 1939- (Pune, India, Grace to India, 2013)
For those of you who want to preach the Word accurately and powerfully because you understand the liability of doing anything less & who are eager to let God speak His Word through you as directly, confrontively, and as powerfully as He gave it & who want to see people transformed radically and living godly lives, there is only expository preaching.
Rediscovering expository preaching / Richard L. Mayhue -- The mandate of biblical inerrancy : expository preaching / John MacArthur, Jr. -- The history of expository preaching / James F. Stitzinger -- The priority of prayer and expository preaching / James E. Rosscup -- The man of God and expository preaching ; The Spirit of God and expository preaching / John MacArthur, Jr. -- Hermeneutics and expository preaching / James E. Rosscup -- Exegesis and expository preaching
Previously published under the title Rediscovering expository preaching.
Includes bibliographical references (pages 315-356) and indexes.
Keywords: Bible -- Homiletical use; Preaching